Impact of glutathione peroxidase and F2-isoprostane on mortality in anemic pediatric septic shock - Setyaningtyas, Arina; Soetjipto; Endaryanto, Anang; Pudjiadi, Antonius Hocky; Handajani, Retno; Kusumastuti, Neurinda Permata; Lestari, Dwi Putri (Acta Biomedica Atenei Parmensis, 2025)
Background and aim: Sepsis is a leading cause of morbidity and mortality in critically ill children worldwide. Several studies have shown that mortality is significantly higher in pediatric septic shock with anemia. In an anemic state, there is also an increase in oxidative stress, which is proved by an increase in the activity of the glutathione peroxidase (GPx) enzyme in pediatric patients with iron deficiency anemia. However, there are only few studies that have specifically examined the role of anemia in pediatric septic shock through oxidative stress. This study aims to investigate the role of oxidative stress in children with septic shock, comparing those with and without anemia. Methods: A cohort of 30 children with septic shock, aged six months to 18 years, were monitored for three days. Glutathione peroxidase and F2-isoprostane levels were measured daily. Twenty-eight days of mortality were recorded. We perform statistical analysis between anemia and non-anemia groups. Results: Of all samples, 15 children were anemic and 15 others were not. Overall mortality was 70%. Anemia has a positive correlation with mortality. Glutathione peroxidase was positively correlated with hemoglobin concentration and negatively correlated with F2-isoprostane. The levels of glutathione peroxidase on day 3 show a significant difference as a predictor of mortality at the cut-off value of 23.56 ng/ml with a sensitivity of 59% and specificity of 60%. Conclusions: Anemia affects mortality in children with septic shock through its effects on oxidative stress.